Use of hardwood mulch applications to improve soil characteristics of Alfisols used in Florida citrus production - Hallman, Lukas M.; Santiago, John M.; Fox, John-Paul; Pitino, Marco; Shatters, Robert G.; Rossi, Lorenzo (Frontiers in Soil Science, 2023)
Introduction: Improving soil fertility is a top priority in Florida’s citrus growing regions, especially in the age of Huanglongbing (HLB; also known as citrus greening). This disease severely reduces fine root mass, causes higher incidences of nutrient deficiencies, and eventually results in the death of affected trees. Additionally, the soils commonly found in Florida’s citrus growing regions are sandy (greater than 98%) and naturally low in fertility, making the nutrient management of HLB-affected trees even more challenging. As a result, interest in organic amendments to increase soil fertility are being tested. Although hardwood chip mulches are successfully used in other regions of the country, no studies exist observing their use on the soils in Florida’s citrus growing regions; therefore, the objectives of this study were to measure the impacts of hardwood oak mulch on (i) Florida Alfisols characteristics and (ii) HLB-affected citrus trees. Methods: A two-treatment field study using 6-year-old ‘Valencia’ sweet orange trees (Citrus × sinensis) grafted on US-812 (C. reticulata × C. trifoliata) rootstock was conducted in Florida’s Indian River District (IRD). The experimental treatment consisted of 0.08 m of hardwood chip mulch sourced from oak trees applied every September for 3 years (2020, 2021, and 2022) while the control treatment had no mulch applied. Soil chemical and physical properties, leaf nutrient concentration, and leaf Candidatus Liberibacter asiaticus (CLas) titer was collected in the fall (October), winter (January), spring (April), and summer (July). Results and Discussion: Overall, after 3 years, oak mulch applications increased soil available phosphorus (32%), potassium (66%), magnesium (71%), organic matter (49%), and moisture (25-88%, depending on the season); however, oak mulch inconsistently impacted leaf nutrient concentrations and was not effective at suppressing HLB. The results show that annual applications of hardwood oak mulch can improve the chemical and physical properties of sandy soils within three years , however, these improvements did not reduce the severity of HLB.